2023
DOI: 10.3390/bdcc7010015
|View full text |Cite
|
Sign up to set email alerts
|

Bias and Unfairness in Machine Learning Models: A Systematic Review on Datasets, Tools, Fairness Metrics, and Identification and Mitigation Methods

Abstract: One of the difficulties of artificial intelligence is to ensure that model decisions are fair and free of bias. In research, datasets, metrics, techniques, and tools are applied to detect and mitigate algorithmic unfairness and bias. This study examines the current knowledge on bias and unfairness in machine learning models. The systematic review followed the PRISMA guidelines and is registered on OSF plataform. The search was carried out between 2021 and early 2022 in the Scopus, IEEE Xplore, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…These techniques are not mutually exclusive and can be combined to improve the model's performance. The technique selection depends on the data type and the specific problem [ 66 ].…”
Section: Artificial Intelligence Techniques In Disease Diagnosis and ...mentioning
confidence: 99%
“…These techniques are not mutually exclusive and can be combined to improve the model's performance. The technique selection depends on the data type and the specific problem [ 66 ].…”
Section: Artificial Intelligence Techniques In Disease Diagnosis and ...mentioning
confidence: 99%
“…For decades, certain professions, including surgery, have been associated predominantly with specific genders or backgrounds. 17,18 Age bias can skew representation of certain age groups, whilst body silhouette bias can perpetuate detrimental beauty standards. In this study, Midjourney mainly demonstrated surgeons as older individuals with narrower body silhouettes.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial that the model can extend its predictions to unobserved data (Murdoch et al, 2019). The generalizability of the model can be determined by evaluating its performance on diverse datasets comprising diverse populations, cultural backgrounds, and age groups (Pagano et al, 2023). A model that performs well across diverse datasets is more likely to be trustworthy and applicable to real-world situations (Acosta et al, 2022;Moor et al, 2023).…”
Section: Acc U R Ac Y a N D Va L I Di T Y Of A I I N M E N Ta L H E A...mentioning
confidence: 99%